Intercostal Nerve Transfers to the Musculocutaneous–A Reliable Nerve Transfer for Restoration of Elbow Flexion in Birth-Related Brachial Plexus Injuries - Lara, Alex Muset; Bhatia, Anil; Correa, Jorge Clifton; Gammal, Tarek Abdalla El (Indian Journal of Plastic Surgery, 2020)
Introduction There is consensus on the need for early microsurgical reconstruction in birth palsies involving three or more roots, that is, extensive partial palsies and total palsies. The fundamental principles of these operations are complete exploration and judicious use of the ruptured stumps by nerve grafting to suitable distal targets. The frequent observation of root avulsions in such cases makes it imperative to look for extraplexual nerve donors for some functions. Intercostal nerves are readily available in such patients.Materials and Methods This is a study of 50 patients of extensive partial and total birth palsies operated upon by the senior author between 1995 and 2010. These included 33 patients with total palsies, 16 patients with near total palsies, and one patient with C56 deficit (operated upon more than 20 years ago). These children were all operated upon between 3 and 6 months of age, except for two patients in whom surgery was delayed till a year due to the phrenic nerve deficit noted at birth. Four intercostal nerves were transferred to the musculocutaneous nerve (MCN) by direct approximation with fibrin glue.Results No respiratory complication was noted from the intercostal harvest. The follow-up ranged from 8 to 20 years (mean 10 years). As many as 48 of the 50 patients regained fully independent elbow flexion. In two cases, the procedure failed completely and had to be salvaged with a free functioning muscle transfer and reuse of the intercostal nerves.Conclusion Intercostal nerve transfers can be relied upon for restoration of elbow flexion in birth palsies. The ruptured roots can then be utilized for augmenting shoulder function in partial palsies or for hand function in total palsies.
Keywords: birth palsies; elbow flexion; intercostal nerve transfers